2020
DOI: 10.1557/jmr.2020.90
|View full text |Cite
|
Sign up to set email alerts
|

Processing a biocompatible Ti–35Nb–7Zr–5Ta alloy by selective laser melting

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 36 publications
2
10
0
2
Order By: Relevance
“…7c), which is the building direction of the sample. The transversal and longitudinal linear intercept lengths, L t = 72 µm and L l = 327 µm, confirm the columnar morphology of the grains in the as-built TNZT sample, as also shown in our previous work [36]. This is related to…”
Section: Phase Constitution and Microstructural Characterizationsupporting
confidence: 90%
See 3 more Smart Citations
“…7c), which is the building direction of the sample. The transversal and longitudinal linear intercept lengths, L t = 72 µm and L l = 327 µm, confirm the columnar morphology of the grains in the as-built TNZT sample, as also shown in our previous work [36]. This is related to…”
Section: Phase Constitution and Microstructural Characterizationsupporting
confidence: 90%
“…Melt pools are clearly observed in Fig. 4a due to microsegregations at the melt pool boundaries, as reported in our previous work [36].…”
Section: Phase Constitution and Microstructural Characterizationsupporting
confidence: 87%
See 2 more Smart Citations
“…As a first result, it was observed that all samples showed excellent ductility under compression and no fracture occurred with strains up to 60%. The Young's modulus and yield strength were compared to results reported in previous works for the TNZT alloy [20,31] and to a β-Ti-24Nb-4Zr-8Sn alloy produced by L-PBF [32].…”
Section: Mechanical Propertiesmentioning
confidence: 99%